Effectiveness of a preventive intervention strategy based on structured telephone interviews in a working population with a moderate to high cardiovascular risk - Sierra, Martha Cabrera; Bonacho, Eva Calvo; García, Ángel García; Moraga, Montserrat Ruiz; Gutiérrez, Juan Carlos Sainz; Barrientos, Antonio Chama; Sánchez-Chaparro, Miguel Ángel (Atención primaria, 2010)
This study assesses the effectiveness of a structured telephone survey on cardiovascular prevention, in modifying lifestyle, on cardiovascular risk parameters, percentage of smoking cessation and overall cardiovascular risk (CVR). Quasi-experimental study of preventive intervention. Ibermutuamur (Spanish Accident and Health Insurance Company). Centres established throughout Spain. A total of 4,792 workers with moderate/high cardiovascular risk who had agreed to be contacted by phone. Subjects with a previous diagnosis of cardiovascular disease and those receiving treatment for hypertension, hypercholesterolemia or diabetes were excluded. A final total of 3,085 workers were contacted and were followed up by telephone surveys on the first, fourth and eighth month after the initial check up (CU) in order to emphasise cardiovascular health advice (Group A); we failed to contact 1,707 workers, who only attended the baseline and one year CUs (Group B). PRINCIPAL OUTCOMES: CUs included medical records and physical examination, with two blood pressure measurements, Body Mass Index (BMI), and biochemical parameters. Cardiovascular risk was stratified following the European cardiovascular SCORE. Individuals with a relative risk higher than 4 were also considered as high-risk. All workers were informed about their cardiovascular risk profile (CVRF) and healthy cardiovascular lifestyle measures. They were also given a letter for their General Practitioner (GP) to inform them on the worker's cardiovascular risk level. A total of 71.5% of the workers were over 45 years, 95.0% males, 76.6% manual workers ("Blue Collar") and 69.7% smokers. Both groups showed improvement in lipid parameters, blood pressure, smoking cessation and overall cardiovascular risk in the second CU. There were significant differences in favour of Group A as regards blood pressure, lipids (except HDL cholesterol), BMI, glycaemia, smoking cessation (A: 23.5%/B: 19.44%, P=0.001) and CVR stratum improvement (A: 46.6%/B: 37.7%, P=0.0001). The large majority (85%) of workers read preventive recommendations; 33% knew their risk level and 73% knew their CVRF. 52.9% gave the letter to the GP, which led them to start therapies on diet (47%), hypertension (19.5%), dyslipidaemia (16.7%), diabetes (4.4%) and smoking (2.9%) and no changes were made in 36.5% of cases. The results of this study suggests that cardiovascular prevention strategy based on structured telephone surveys on high/moderate CVR subjects to promote lifestyle changes could be effective at reducing CVR. A clinical trial is required for confirmation. Sending information on CVRF following routine medial CUs and Primary Care involvement, could contribute to the positive changes observed.